Depression level and coping responses toward the movement control order and its impact on quality of life in the Malaysian community during the COVID-19 pandemic: a web-based cross-sectional study - Anne, Yee; Nur‘Aqilah, Mohd Hodori; Tung, Yu Zhen; Ooi, Po Lin; Saiful Adni, Abdul Latif; Husna, Md Isa; Diana Ng, Leh Ching; Chai, Chee Shee; Tan, Seng Beng (BioMed Central Ltd., 2021)
Background: Coronavirus 2019 disease (COVID-19) is a highly infectious disease prompting extreme containment measures, including lockdown, travel restrictions, social distancing, and stringent personal hygiene. This study inves‑ tigates the depression level and coping responses toward the lockdown, referred as the movement control order (MCO) during COVID-19 pandemic in Malaysia and its impact on quality of life. Method: This cross-sectional study was conducted from April to May 2020. The outcomes were assessed using the Depression, Anxiety and Stress Scale–21, Coping Orientation to Problems Experienced Inventory, and World Health Organisation Quality of Life–BREF Scale (WHOQOL-BREF) in both English and validated Malay versions. Results: Mild-to-severe depression was found in 28.2% (n=149) of the 528 respondents. Respondents with mild-tosevere depression were signifcantly younger (33.09±10.08 versus 36.79±12.47 years), without partner (71.8% versus 45.6%), lived in the red zone (85.9% versus 71.0%), and had lower household income as defned in the category of B40 (51.7% versus 39.3%) compared to those without depression (all p<0.01). The avoidant coping score was signif‑ cantly higher (25.43±5.69 versus 20.78±5.65), while the religious coping score was signifcantly lower (5.10±2.07 versus 5.94±2.11) among those with mild-to-severe depression compared to those without depression (both p<0.001). Respondents with mild-to-severe depression also had signifcantly lower mean score in each domain of WHOQOL-BREF compare to those without depression [(physical health, 13.63±2.66 versus 16.20±2.11), (psychologi‑ cal, 12.5±2.79 versus 16.10±2.14), (social relationships, 12.17±3.49 versus 15.28±2.93), environment (14.50±2.39 versus 16.21±2.14), all p<0.001] after controlling for age, marital status, zone, household income, and coping scores. Conclusion: COVID-19 lockdown had adverse mental health efects. Our study highlighted that approximately one in three individual experienced mild-to-severe depression during the nationwide MCO. The varied impact of the pan‑ demic on mental health could be due to diferent population characteristics and coping strategies used. Identifying those at higher risk to develop depression during MCO for COVID-19 pandemic could help mental healthcare service providers to plan services for those susceptible, thereby mitigating the pandemic’s efect on quality of life.